People with higher systemizing traits have wider right hands - Chen, Na; Hidaka, Souta; Ishii, Naomi; Wada, Makoto (Frontiers in Psychiatry, 2024)
Introduction Various genetic mutations have been implicated in autism spectrum disorder (ASD). Some candidate genes for ASD are known to be related to signal transduction and may be involved in hand development as well as neurodevelopment. Therefore, although subtle, anatomical variations in hand configurations may be observed in individuals with ASD. However, except for research on the finger ratio, which has been suggested to be related to prenatal sex hormone exposure, only few studies have been conducted. Given the spectrum characteristics of ASD, we explored whether hand configurations are associated with ASD-related traits in the general population. Methods Photographs of the dorsal surface of each hand were obtained, and the distances between the metacarpophalangeal joints and finger lengths were measured. The Autism Spectrum Quotient, Empathy Quotient, and Systemizing Quotient were used to evaluate ASD-related traits. Results We found a significant positive correlation between the aspect ratio of the right hand and the Systemizing Quotient score: individuals with a larger width relative to the finger length showed more systemizing traits. Discussion These findings suggest that gene polymorphisms or prenatal sex hormone exposure may underlie the relationship between systemizing traits and hand configurations.